2019
DOI: 10.1096/fj.201802137rrr
|View full text |Cite
|
Sign up to set email alerts
|

Kartogenin preconditioning commits mesenchymal stem cells to a precartilaginous stage with enhanced chondrogenic potential by modulating JNK and β‐catenin–related pathways

Abstract: Cartilage engineering strategies using mesenchymal stem cells (MSCs) could provide preferable solutions to resolve long‐segment tracheal defects. However, the drawbacks of widely used chondrogenic protocols containing TGF‐β3, such as inefficiency and unstable cellular phenotype, are problematic. In our research, to optimize the chondrogenic differentiation of human umbilical cord MSCs (hUCMSCs), kartogenin (KGN) preconditioning was performed prior to TGF‐β3 induction. hUCMSCs were preconditioned with 1 µM of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…introduced to further confirm the interaction between the Rac1 and Wnt/β-catenin pathway in rat EPCs. As shown in Figure 5A 30 And the result of immunofluorescence staining of collagen II was in accordance with the mRNA results ( Figure 5B,C).…”
Section: Moreover Wnt/b-catenin Signalling Inhibitor and Activator Weresupporting
confidence: 83%
See 1 more Smart Citation
“…introduced to further confirm the interaction between the Rac1 and Wnt/β-catenin pathway in rat EPCs. As shown in Figure 5A 30 And the result of immunofluorescence staining of collagen II was in accordance with the mRNA results ( Figure 5B,C).…”
Section: Moreover Wnt/b-catenin Signalling Inhibitor and Activator Weresupporting
confidence: 83%
“…Moreover, Wnt/b‐catenin signalling inhibitor and activator were introduced to further confirm the interaction between the Rac1 and Wnt/β‐catenin pathway in rat EPCs. As shown in Figure A, real‐time PCR analysis showed that Wnt/b‐catenin signalling inhibitor XAV‐939 (10 μmol/L) could mimic the effects of NCS23766, which increased the expression of aggrecan and collagen II and decreased the expression of MMP13 and ADAMTS5 after IL‐1β stimulation, while Wnt/b‐catenin signalling activator SKL2001 (40 µmol/L) could rescue the effects of NCS23766 . And the result of immunofluorescence staining of collagen II was in accordance with the mRNA results (Figure B,C).…”
Section: Resultssupporting
confidence: 52%
“…While TGF-β1 or KGN alone did not yield positive outcomes, the authors found that a combination of TGF-β1, BMP-7 and KGN worked synergistically to drive rat BMSC chondrogenesis 7 . A potentially more relevant study published in 2019 reported that preconditioning of human umbilical cord-derived mesenchymal stromal cells in medium supplemented with 1 µM KGN enhanced their chondrogenic response to TGF-β3 21 . Similar to our observations with human BMSC, treatment of human umbilical cord-derived mesenchymal stromal cells with KGN alone was not chondrogenic.…”
Section: Discussionmentioning
confidence: 99%
“…[21,22] Another study also demonstrated that KGN could increase type-I collagen synthesis in the dermis of BALB/C mice in vivo through activation of the smad4/smad5 signaling. [23,24] Furthermore, some other studies have demonstrated that KGN may also stimulate proliferation of several stem cells types originated from none-cartilage tissues. [25] Whether the proliferation of MSC or chondrogenic progenitor cells also plays a significant role in cartilage regeneration remains unknown.…”
Section: Introductionmentioning
confidence: 99%